Silence in court!: non -verbal communication in a Zimbabwean court of law - Saidi, Umali; Pfukwa Charles (Unisa Press, 2017)
A court of law is full of drama and rituals with a lot of perlocutionary effects. This article focuses on non-verbal communication which is an important aspect of semiotics and speech acts in legal discourse. The article first define and briefly discusses Ferdinand de Saussure’s contribution to semiotics. It goes on to discuss his description of the relationship between two pairs of important concepts in semiotics, the signifier and the signified as well as Charles Sanders Peirce’s three basic kinds of signs, namely: the icon, the index and the symbol. John Austin’s speech acts will also be discussed from the spectra of discourse analysis given that a court of law provides, among others, the basis for legal discourse. The article further argues that the behaviour and actions of the members of the legal discourse community found in a court of law are ‘culturally’ determined; with different cultures having different ways of expressing and interpreting reality. It then examines some aspects of the non-verbal code in a Zimbabwean court of law such as dress codes, movement, space and how these convey messages that can influence the outcome of a case.